DEVELOPMENT OF GERMAN-AMERICAN RELATIONS DURING ANGELA MERKEL’S CHANCELLORSHIP - A. P. Nagdaseva (Дискурс, 2018)
The article analyzes relations between Germany, the U.S. and NATO that are the basis of transatlantic links. After the Cold War finished and Germany reunited, Berlin has pursued a more independent foreign policy and has advocated NATO's transformation into a "balanced Euro-American alliance". Angela Merkel as a new head of the German government (since 2005) managed to considerably narrow differences in bilateral relations. German leaders seek to expand its political and economic influence in the world, which is only possible within the context of strengthening German-American relations and solidarity within the North Atlantic Alliance. Mutually beneficial economic relations and strong position of Germany in the EU increase the role of the country in the transatlantic relations.